Evaluation of a radiographer‐led peripherally inserted central catheter insertion service. Issue 4 (9th February 2020) - De Boo, Diederick W; Marshall, Elissa; Erskine, Brendan; Koukounaras, Jim; Kavnoudias, Helen; Thomson, Kenneth R
Abstract: Introduction: To evaluate a radiographer‐led peripherally inserted central catheter (PICC) insertion service within an interventional radiology suite using ultrasound and fluoroscopic guidance. Methods: Data from 366 consecutive PICC insertions by five trained angiography‐specialized radiographers were prospectively collected over a 12‐month period. For each PICC insertion, patient demographics, including past medical history of cystic fibrosis (CF), number of punctures, vein used, final tip position, contrast administration and screening time were recorded. Institutional review board approval was obtained. Results: The overall PICC insertion success rate was 100%. Fifty‐five (15%) had a known medical history of CF. Three hundred and thirty‐one (90%) PICC insertions required a single puncture and 32 (9%) required two punctures. The remaining three insertions required three punctures. The basilic vein was most commonly used (69%) followed by the brachial vein (29%), and the cephalic vein was used only in 2%. Administration of contrast medium was necessary during 27 (7%) PICC insertions. Mean screening time was 10.7 s. Conclusion: Our specifically trained, radiographer‐led PICC insertion service proved to be successful. Both straightforward and complex insertions, for example in CF patients could be adequately and efficiently performed.